Vocabulary of Rural Life of Bessarabian Germans in Danube Region (1814/1940) in Accident Reports: Array - Golovina, Natalia (Journal of Danubian Studies and Research, 2021)
This article analyzes accident reports in the German colonies of Bessarabia (1814/1940), dated to the second half of the 19th century. The object of study is the problem of the relationship between language and culture, which is displayed in the structure of the text and makes it possible to establish the features of the way people exist, their knowledge, experience, result of activities and traditions. The question of the specifics of the vocabulary of accident reports in the colonies of German colonists in the south of Bessarabia continues to study German discourse in conditions of its separation from the main range and is an important element in realizing the task of its reconstruction and preservation. The paper uses the approach of observing the lexical-semantic microfield “rural life” and its linguocultural description. The results of the work are of interest for the lexicology of the German language (sections: semantics, onomastics, word formation), regional studies of Germany, regional studies, as well as the history of Ukraine and has implications of theoretical and practical training of students in the specialty “German language”. The value of the work is its novelty, relevance of the chosen topic, as well as the author’s original approach to the analysis of the lexical level of historical texts using cultural commentary related to objects of the nomination of rural household items of German colonists.